Behavioural and electrophysiological responses of Philaenus spumarius to odours from conspecifics - Milos Sevarika; Gabriele Rondoni; Sonia Ganassi; Onofrio Marco Pistillo; Giacinto Salvatore Germinara; Antonio De Cristofaro; Roberto Romani; Eric Conti (Scientific Reports, 2022)
Abstract The meadow spittlebug, Philaenus spumarius L. (Hemiptera: Auchenorrhyncha: Aphrophoridae), is the main vector of Xylella fastidiosa subsp. pauca strain ST53, the causal agent of the Olive Quick Decline Syndrome. Philaenus spumarius and other Auchenorrhyncha are known to communicate via vibrations, whereas the possible occurrence of semiochemical communication has been poorly investigated so far. Through a chemical ecology approach, we provide evidence of intraspecific chemical communication in P. spumarius. In Y-tube olfactometer bioassays, males were attracted to unmated females as well as toward the headspace volatile extracts collected from unmated females. Conversely, females did not respond to unmated male volatiles or their extracts, nor did males and females respond to volatiles from individuals of the same sex. Electroantennography assays of unmated male and female headspace extracts elicited measurable responses in the antennae of both sexes. Male responses to body wash extracts from both sexes were stronger compared to female responses. Thus, suggesting the presence of compounds that are highly detected by the male’s olfactory system. The female head seemed to be the source of such compounds. This is the first record of intraspecific chemical communication in P. spumarius and one of the very few records in Auchenorrhyncha. Possible biological roles are under investigation.